Percepção de pessoas que fizeram uso de drogas (álcool, maconha e crack) sobre o estigma a que estão sujeitos na sociedade - Gonçalves, Janaina Rubio [UNIFESP] (2019)
Introduction: In the contemporary world, drugs, in a simplistic way, were classified as licit and illicit, making the sale and consumption of a group of psychoactive substances prohibited. Considered major villains in public health, illegal drugs bring serious consequences to the user. Besides the punishment of those who consume them, they produce and market the marginalization and stigmatization generated by society in relation to this population, are some of these great damages, creating barriers in the quality of treatment, recovery and social reintegration of these users. Objective: This study aims to analyze and identify the perceptions of people who have used alcohol, marijuana or crack cocaine in relation to stigma and prejudice. Method: This is a qualitative research, developed through in-depth interviews. The theoretical saturation point technique was used as indicative that the sample was sufficient. The interviews were literally transcribed, inserted and analyzed by the software NVivo 10, with data exploration, using the technique of content analysis. Results/Discussion: The three groups experienced some kind of stigma/discrimination/prejudice in some sphere of life. The family, school and health professionals had different reactions with the users interviewed, depending on the drug in question. The view of lack of character and little collaboration to cease use compromised the relationship of these spheres with the users interviewed. Crack has awakened the most intense and violent stigma, sometimes leading the user to social exclusion. Marijuana stigma was mild and there was a tolerance for use. Reports of actions that compromise the lives of these users were non-existent. Alcohol also generated stigma, especially from health professionals, who did not believe in the recovery of these users. Conclusion: The stigma interfered in the life of the research participants in a definitive way, modifying several outcomes, such as the performance in treatment, school and family relationship. Stigma has often contributed to increased drug use, dropping out of school and treatment and abandonment of the home. Instances that should protect the user from stigma directed at them by society, have absorbed common sense and they behaved in a similar way, but generating greater harm by the meaning and ascension they have in the lives of these participants.